2022
DOI: 10.3390/pharmaceutics14050918
|View full text |Cite
|
Sign up to set email alerts
|

Improved Efficiency of Pomegranate Seed Oil Administrated Nasally

Abstract: Pomegranate seed oil (PSO) is currently administrated orally as a food supplement for improving memory. However, the efficiency of the oral dosage forms for such purposes is low, mainly due to the blood brain barrier impeding a good delivery to brain. In this work, we designed and characterized a PSO phospholipid oily gel for nasal administration. We tested the performance of the new PSO delivery system in animal models for impaired memory and locomotor activity. The experimental results indicated a statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Auerbach et al also reported changes in estradiol, FSH, luteinizing hormone (LH), prolactin, progesterone, testosterone, and thyroid‐stimulating hormone (Natsheh & Touitou, 2022) in their study after 12 weeks of PSO consumption. Detected changes between the two groups were not significant in any of the parameters.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Auerbach et al also reported changes in estradiol, FSH, luteinizing hormone (LH), prolactin, progesterone, testosterone, and thyroid‐stimulating hormone (Natsheh & Touitou, 2022) in their study after 12 weeks of PSO consumption. Detected changes between the two groups were not significant in any of the parameters.…”
Section: Resultsmentioning
confidence: 94%
“…In the study by Kapoor et al (2015) (Natsheh & Touitou, 2022) in their study after 12 weeks of PSO consumption. Detected changes between the two groups were not significant in any of the parameters.…”
Section: Narrative Review Of the Studiesmentioning
confidence: 99%
“…The oil composition of pomegranate seed has lately garnered special attention due to its abundance of antioxidant and anticancer compounds, which might be key components in the development of novel treatments and cosmetics. Because of its nutritional and therapeutic characteristics, pomegranate seed oil is utilized as a functional component in the food, pharmaceutical, and feed sectors. , PSO is a rich source of poly- and monounsaturated fatty acids, which explains its antioxidant, anti-inflammatory, and neuroprotective activities. , The combination of PSO and ketoprofen in the self-nanoemulsifying system is suggested to enhance the therapeutic effect of the drug. Further in vivo pharmacodynamic studies are required to assess the anti-inflammatory and analgesic effects of this promising combination.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 PSO is a rich source of poly-and monounsaturated fatty acids, which explains its antioxidant, anti-inflammatory, and neuroprotective activities. 31,32 The combination of PSO and ketoprofen in the self-nanoemulsifying system is suggested to enhance the therapeutic effect of the drug. Further in vivo pharmacodynamic studies are required to assess the anti-inflammatory and analgesic effects of this promising combination.…”
Section: D Printing Of the Capsule Shellsmentioning
confidence: 99%
“…The number of crossed squares was counted during 5 min with no habituation session. Animals treated with effective neuroprotective drugs are expected to cross more squares. , …”
Section: Methodsmentioning
confidence: 99%